Production- and consumption-based carbon emission decoupling and decomposition of the Belt and Road countries - Zhang, Jianpeng; Han, Mengyao (Frontiers in Environmental Science, 2022)
The Belt and Road Initiative (BRI) provides a platform for developing countries with huge growth potentials, which may also face huge carbon emission pressure while achieving rapid economic growth. Given certain similarities in economic patterns and resource endowments, this study aims to trace carbon emission decoupling and decomposition of different countries/regions within the Belt and Road area and provide new insights into the drivers of carbon emission decoupling from both production- and consumption-based perspectives. Based on the multi-regional input-output modelling and Tapio decoupling decomposition, this study quantitatively analyzes the decoupling evolution and decomposition drivers of economic activities and carbon emissions in countries along the Belt and Road. From the results, the production-based carbon emissions of the Belt and Road countries was significantly higher than the consumption-based carbon emissions. The increasing rate in the production-based carbon emissions was also faster than the consumption-based one, with an increasing huge gap between the two sides. Regarding the spatial distribution of carbon emissions, the regions with huge amounts of carbon emissions mainly distributed in Russia, Iran, South Korea, and Saudi Arabia. When compared, the consumption-based carbon emissions of China and Russia were the highest, followed by those of the countries in Central Asia and West Asia. Compared with the production-based side, the decoupling rate of the Belt and Road countries was slower than the consumption-based one. The Belt and Road countries mainly maintained in the weak decoupling status, with the economic effect as the main driver in carbon emission growth, and the energy intensity effect as the dominated contributor in carbon emission reduction. Through exploring the decoupling and decomposition of production- and consumption-based carbon emissions within the Belt and Road countries, this study attempts to provide certain implications for the low-carbon transition and sustainable development within the countries along the Belt and Road.